Shape-Based Matching: Application of Defect Detection - Harun, Mohamad Haniff; Sulaiman , Marizan; Hairol Nizam , Mohd Shah (2011)
This research is regarding to the application of a vision algorithm sensor to monitor the operation of a system in order to control the concerning jobs and work pieces recognition that are to be made during system operation in real time. This paper stresses more on the vision algorithm that mainly focus on shape-based matching application. The algorithm consists of two parts; training phase and recognition phase. The main focus of this paper is to create a region of interest at which they are able to adapt to a variety of applications and purposes depending on the needs of users. The system will be tested using several images that have a variety of characteristic and properties in developing a better system for industrial application. There are three types of glue defect; gap, bumper and bubble are trained through the systems in order to store their own characteristics and properties in the system for matching purposes. The matching process will take place for determine the results occur in recognizing the defects after gluing process being done.